APLIKASI KONSEP NEGARA HUKUM DAN DEMOKRASI DALAM PEMBENTUKAN UNDANG-UNDANG DI INDONESIA - Fauzi Iswari (JCH (Jurnal Cendekia Hukum), 2020)
The involvement of the people in determining public policies, such as in the formation of laws, is a reflection of the state that synergizes law and democracy. This research aims to describe the application of the concept of a rule of law and democracy in the formation of laws in Indonesia. This type of research is normative legal research in which data is obtained from library materials or secondary data. The data analysis techniques (legal materials) used are qualitative analysis. From the results of the research conducted, it can be understood that the application of the principles of rule of law and democracy in the formation of laws in Indonesia, is ideally reflected in the application of the principles of legality, the principle of legal certainty, and the protection of human rights in a law. Meanwhile, the principle of democracy in the formation of laws can be seen from the existence of public involvement or participation in the formation of a law. However, what is happening in Indonesia today is that the formation of laws has led to indifference to the principles of a rule of law and democracy. This has resulted in protests and rejection of laws that have been passed as well as against bills being discussed in the legislative.